Field notes contributed by Raymond L. Cummins, summer 1996 - Cummins, Raymond L.et al (1996)
List of birds and locations contributed by Raymond L. Cummins. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1996. Epson - sheet feed